Evaluation of Companion Diagnostics in Scientific Advice and Drug Marketing Authorization Applications by the European Medicines Agency - Maliepaard, Marc; Nibi, Priscilla; Nibi, Gabrièlla; Pasmooij, Anna M. G. (Frontiers in Medicine, 2022)
With the implementation of the new EU regulation on in vitro diagnostics (IVDR) in May 2022, notified bodies will be required to assess Companion Diagnostics (CDx). The EMA and national medicines agencies will be consulted on the performance and safety of CDx. In this paper, we report on our systematic review on how the EMA has dealt with CDx in dossiers for marketing authorization procedures, in 2017–2019, and in scientific advice procedures in 2016–2020, prior to the implementation of the new IVDR. Out of 167 medicines approved or refused by the EMA, CDx played a role for 20 medicines during assessment. Both European public assessment reports (EPARs) and the internal day 80 and day 120 assessment reports (ARs) of the EMA centralized marketing authorization procedures for these 20 medicines were analyzed in detail to determine how CDx were assessed. Likewise, in 46 of 159 cases in which scientific advice was provided, CDx were mentioned in the question-and-answer section of the scientific advice, and these were analyzed in an analogous manner. Our analysis indicates that clinical performance and analytical performance of the CDx were the most-discussed topics, being discussed 11 and seven times in the 20 EPARs and 59 and 29 times in the ARs, respectively. For scientific advice, clinical and analytical performance was discussed 65 and 22 times in the 46 retrieved mentions of scientific advice. Other aspects in relation to CDx were discussed as well, although at a lower frequency, in assessment reports and scientific advice. Overall, our analysis demonstrates that, despite the absence of an obligation from a legal point of view, EMA has gained experience on the assessment of CDx, most notably regarding its analytical and clinical performance. This experience may be useful in situations in which the EMA and national agencies of EU member states will formally be consulted by notified bodies regarding the performance and safety of CDx. In addition, the issues raised in the EPARs, ARs and scientific advice reports provide insight for applicants on aspects of CDx that need careful consideration.